2010
DOI: 10.1037/a0018220
|View full text |Cite
|
Sign up to set email alerts
|

Examining the construct validity of the Psychopathic Personality Inventory–Revised: Preferential correlates of fearless dominance and self-centered impulsivity.

Abstract: Although the construct of psychopathy is frequently construed as a unitary syndrome, the Psychopathic Personality Inventory (PPI; Lilienfeld & Andrews, 1996) and its revision, the PPI-R (Lilienfeld & Widows, 2005), are composed of 2 scales, termed Fearless Dominance (FD) and Self-Centered Impulsivity (SCI), which appear to reflect orthogonal dimensions. In this study, we examined the construct validity of the FD and SCI scales of the PPI-R as markers of these constructs with a range of theoretically relevant c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
79
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(91 citation statements)
references
References 59 publications
10
79
0
2
Order By: Relevance
“…There is evidence for the convergent and discriminant validity of the PPI-R with respect to Levenson's SelfReport Psychopathy Scale (LSRP; Levenson, Kiehl, & Fitzpatrick, 1995), and the SelfReport Psychopathy Scale-II (SPR-II, Hare, 1985). Support for the construct validity of the PPI-R is also evident in associations between this scale and theoretically relevant subscales from measures such as the PAI (e.g., Antisocial Features, Aggression, and Dominance) and the NEO-Five-Factor Inventory (NEO-FFI; Costa & McCrae, 1992; e.g., Negative Relationships with Agreeableness and Conscientiousness; DeMauro & Leung, 2005;Lilienfeld & Widows, 2005) and the Brief Psychiatric Rating Scale (Edens & McDermott, 2010).…”
Section: Psychopathic Personality Inventory-revisedmentioning
confidence: 95%
“…There is evidence for the convergent and discriminant validity of the PPI-R with respect to Levenson's SelfReport Psychopathy Scale (LSRP; Levenson, Kiehl, & Fitzpatrick, 1995), and the SelfReport Psychopathy Scale-II (SPR-II, Hare, 1985). Support for the construct validity of the PPI-R is also evident in associations between this scale and theoretically relevant subscales from measures such as the PAI (e.g., Antisocial Features, Aggression, and Dominance) and the NEO-Five-Factor Inventory (NEO-FFI; Costa & McCrae, 1992; e.g., Negative Relationships with Agreeableness and Conscientiousness; DeMauro & Leung, 2005;Lilienfeld & Widows, 2005) and the Brief Psychiatric Rating Scale (Edens & McDermott, 2010).…”
Section: Psychopathic Personality Inventory-revisedmentioning
confidence: 95%
“…Marcus et al, 2013). In contrast to PCL-R Factor 1, PPI-R Fearless Dominance shows negative associations with anxiety indices and questionnaires (Benning et al, 2003;Benning, Patrick, Blonigen et al, 2005;Edens & McDermott, 2010;Lilienfeld & Widows, 2005;Patrick, Edens, Poythress, Lilienfeld, & Benning, 2006;Ross et al, 2007;Uzieblo, Verschuere, & Crombez, 2007;Uzieblo, Verschuere, Van den Bussche, & Crombez, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In a sample of 758 college students a three-factor model (PPI-I, PPI-II, and Coldheartedness) has been derived with the PPI-SF (Smith, Edens, & Vaughn, 2011). Studies have suggested that PPI-I is strongly positively associated with interpersonal dominance, and negatively related to internalizing psychopathology, including anxiety and depression (Benning, Patrick, & Iacono, 2005;Edens & McDermott, 2010;Lilienfeld & Widows, 2005). In contrast, PPI-II tends to be positively correlated with internalizing measures and is positively correlated with externalizing measures including impulsivity, hostility, and aggression (Edens & McDermott, 2010;Lilienfeld & Widows, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have suggested that PPI-I is strongly positively associated with interpersonal dominance, and negatively related to internalizing psychopathology, including anxiety and depression (Benning, Patrick, & Iacono, 2005;Edens & McDermott, 2010;Lilienfeld & Widows, 2005). In contrast, PPI-II tends to be positively correlated with internalizing measures and is positively correlated with externalizing measures including impulsivity, hostility, and aggression (Edens & McDermott, 2010;Lilienfeld & Widows, 2005). Behavioral genetic studies have indicated that PPI-I was associated with a reduced genetic risk for internalizing disorders, and PPI-II was associated with an increased genetic risk for externalizing disorders (Blonigen, Hicks, Krueger, Patrick, & Iacono, 2005).…”
Section: Introductionmentioning
confidence: 99%